How to Deal With Chronic Patellar Instability: What Does the Literature Tell Us? - Sanchis-Alfonso, Vicente (Sports Health, 2016)
CONTEXT: Patellar instability is a common clinical problem, affecting between 7 and 49 people per 100,000. However, not all patellar instabilities are equal, the etiology of the disorder is multifactorial, and a clear understanding of the cause of instability is crucial for appropriate surgical treatment. The goal of this article is to identify how to best treat patellar instability to provide good outcomes and hopefully prevent future osteoarthritis. EVIDENCE ACQUISITION: A PubMed search from 1983 through May 2015. STUDY DESIGN: Clinical review. LEVEL OF EVIDENCE: Level 4. RESULTS: Several subpopulations of patients with chronic patellar instability exist: (1) lateral patellar instability during the early arc of knee flexion (0°-30°), (2) lateral patellar instability persisting beyond 30° of knee flexion, (3) lateral patellar instability in greater knee flexion, and (4) medial patellar instability. In patients with lateral instability during the early arc of knee flexion, the medial patellofemoral deficiency is the essential lesion. Persistent instability beyond 30° of knee flexion suggests an unusually high patella, severe trochlear dysplasia, pathologic increment of the tibial tuberosity–trochlear groove distance, or a combination of these factors. In patients with lateral instability in greater knee flexion, increasing and unbalanced tension in the extensors pulls the patella out of the groove as the knee is flexed. Finally, medial patellar instability is an objective iatrogenic condition that appears after realignment surgery in the vast majority of cases. CONCLUSION: The etiology of chronic patellar instability is multifactorial, and its treatment must therefore be personalized. STRENGTH OF RECOMMENDATION TAXONOMY (SORT): B.